Exploring Students’ Voices on The Use of Chatgpt as A Speaking Partner in English Practice: Penelitian - Vivi Ayu Lestari; Anwar Hilman; Arif Budimansyah Purba; Ahmad Najib Mutawally; Rizki Teja Pratama; Iksan Khasani; Ludovikus; Deden Moh Alfiansyah; Deliana Febriani; Inpresta Natalia; Sekarlita Indriani; Cepi Indra Grahana; Juni Adi Putra (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study investigates university students’ perceptions of ChatGPT as a speaking partner in English-speaking practice. Employing a qualitative research design, the study involved English major students at Horizon University Indonesia who engaged in ChatGPT-assisted speaking activities for four weeks. Data were collected through semi-structured interviews and reflective journals and analyzed using thematic analysis to examine students’ perceptions, perceived benefits and challenges, and the impact of ChatGPT on their motivation and speaking confidence. The findings reveal that students generally perceived ChatGPT as a helpful, accessible, and non-judgmental speaking partner. Its use provided increased opportunities for speaking practice, facilitated vocabulary development, and offered immediate feedback, which contributed positively to students’ motivation and confidence. Nevertheless, challenges were identified, including limited emotional interaction, occasional unnatural responses, and difficulties in sustaining extended contextual conversations. Overall, the study concludes that ChatGPT can function as an effective supplementary tool in English-speaking practice, particularly when integrated with appropriate pedagogical guidance to support EFL learners’ oral communication in higher education.